Late Holocene Indian summer monsoon evolution and centennial fluctuations inferred by grain-size sensitive component from Lake MangCo, southeastern Tibetan Plateau - Ning, Dongliang; Sun, Weiwei; Wan, Dejun; Cheng, Longjuan; Jiang, Qingfeng (Frontiers in Earth Science, 2025)
Identifying the late Holocene Indian summer monsoon (ISM) changes and their possible forcing mechanisms provides an important perspective for understanding the current monsoon shifts driven by anthropogenic climate change within a natural baseline. In this study, we present a well-dated, ca. 4.0 ka grain-size sensitive component record from Lake MangCo, located in the southeastern Tibetan Plateau. The record depicts late Holocene ISM evolution and centennial-scale precipitation events superimposed on millennial-scale climate changes. The results indicate that precipitation was relatively high during the first half of the late Holocene, likely before 2.0 cal ka BP, followed by a period of relatively reduced precipitation thereafter, which indicates that the Northern Hemisphere summer insolation (NHSI) has primarily controlled ISM intensity. A slight increasing trend in ISM strength since 1.1 cal ka BP was observed, which may correspond to the reported “2.0-kyr-shift” and could be related to warming tropical temperatures. Three low precipitation intervals, occurring at ∼1.1, 2.0, and 3.2 cal ka BP, align well with known centennial-scale ISM weakening events during the late Holocene, such as the Medieval Warm Period (MWP) and the “2.0-ka-dry-event.” Our findings further validate the climatic effects of tropical ocean–atmospheric interactions in the Pacific and Indian Ocean basins on ISM variabilities at centennial timescales.